Routines, Time Dedication and Habit Changes in Spanish Homes during the COVID-19 Lockdown. A Large Cross-Sectional Survey - Miguel Ángel Navas-Martín (MDPI AG, 2021)
Many countries chose to establish social distancing as lockdowns after the COVID-19 outbreak. Households had to adapt their day-to-day lifestyles to new circumstances, affecting routines and time dedication to tasks. This national study was carried out to find out how the confinement by COVID-19 affected Spanish households on the perceived habit changes during this period, in relation to their socio-demographic characteristics and household composition. An online questionnaire was launched during the COVID-19 lockdown, from 30 April to 22 June 2020. Descriptive statistics were analyzed, stratified by gender, on time dedication, routine, home leaving, and habit change variables. Chi-square tests were used to explore the relations of significance with socio-demographic characteristics and home composition. All contrast analyses were performed for a 95% confidence level (significance considered for p < 0.05). In total, 1673 respondents participated from different age groups, educational level, employment status and household composition. Sixty percent of respondents maintained their routines. A third tried to establish a new one, being related to women, young people, not a university student, and living with others, including minors. Regarding dedication to tasks, adults aged 35–54 years, with more cohabitants, especially women, devoted themselves intensively to the home or to care, while those under 35 were dedicated more to rest, leisure, television or reading. People with university studies were more related to teleworking. The frequency of going outside was related to gender, age, educational level and living with elders, specifically for grocery shopping and taking out garbage. Changes in habits, routines and time dedication in confinement were strongly linked to the sociodemographic and coexistence conditions in Spanish homes. The greatest impacts were suffered by women, people with children, and adults between 35–54 years of age, especially on care and domestic chores.